Pengaruh Penyesuaian Diri dan Dukungan Sosial terhadap Motivasi Belajar Mahasiswa Fakultas Ekonomi yang Merantau - Rahmalika Putri Anjani; Marsofiyati Marsofiyati; Eka Dewi Utari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to analyze the role of social support on learning motivation among migrant students at the Faculty of Economics, Jakarta State University class of 2022. Migrant students often face challenges in the form of adapting to a new environment, which can influence their learning motivation. Social support, whether from family, friends, or the campus environment, is an important factor in helping this adaptation process. This research identifies types of social support such as emotional, instrumental, informational and self-esteem support, and their influence on learning motivation. Based on existing literature, social support can increase students' self-confidence, which has an impact on higher enthusiasm and motivation to learn. On the other hand, a lack of social support has the potential to cause stress, low self-confidence, and loss of motivation to learn. Using the case study method, this research examines the relationship between social support and the learning motivation of migrant students. The research results show that social support has a positive correlation with learning motivation. External factors, such as the campus environment and lecturers' teaching methods, as well as internal factors, such as personal interests and suitability of the field of study, also influence student learning motivation. This research is expected to provide new insights in increasing the learning motivation of migrant students through strengthening social support.